ANALYSIS OF HOUSEHOLD VEHICLE OWNERSHIP AGAINST CONFLICT IN MANGGALA DISTRICT MAKASSAR CITY - Lambang Basri Said; Maryam H; Sri Indriyani (Moeslim Indonesian University (UMI), 2018)
The increase in population accompanied by economic growth in Bumi Tamalanrea Permai Housing (BTP) has pushed the level of motorized vehicle ownership from year to year to increase. This of course will have an effect on the existing traffic conditions. So the objectives to be achieved in this study are: to analyze the socio-economic and demographic characteristics of households in Manggala District and to analyze the vehicle ownership model in households with the factors that influence it. The number of family members is 5 people or more, by 35.2%. And 1 person with a total percentage of 2.8%. the percentage who work 2 people is 40.4%. The highest number of family members who are students/students is 1 person with a percentage value of 38.8%. The highest monthly net income of Rp. 6 million - Rp. 10 million, which is 28.4%. Meanwhile, the gross income per month is Rp. 6 million – Rp. 10 million, which is 31.6%. The average distance per day is 10-20 km, with a percentage of 35.2%. The average monthly transportation cost per household is IDR 500 thousand – IDR 1 million, with a percentage of 39.2%. Average travel time per day is 1-2 hours, with a percentage of 40.8%. The highest level of household car ownership in Manggala District is 1 unit, with a percentage of 49.2%. While the smallest is more or equal to 4 units with a percentage of 0.4%. The highest level of motorcycle ownership in each household in Manggala District is 1 unit, with a percentage of 40.8%. While the smallest is more or equal to 4 units with a percentage of 1.2%.